2021
DOI: 10.1016/j.jbc.2021.100572
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of PHGDH via the catalytic unit is essential for its enzymatic function

Abstract: Human D-3-phosphoglycerate dehydrogenase (PHGDH), a key enzyme in de novo serine biosynthesis, is amplified in various cancers and serves as a potential target for anticancer drug development. To facilitate this process, more information is needed on the basic biochemistry of this enzyme. For example, PHGDH was found to form tetramers in solution and the structure of its catalytic unit (sPHGDH) was solved as a dimer. However, how the oligomeric states affect PHGDH enzyme activity remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
3
10
0
Order By: Relevance
“…PHGDH protein was expressed in resting and stimulated MDDCs. Consistent with the dimerization of PHGDH in the presence of substrate [ 37 ], Western blot carried out in native conditions in a non-denaturing and non-reducing buffer showed the presence of the 55-kD PHGDH band as well as a band compatible with dimerization and constitutive 3-phosphoglycerate flux ( Fig. 6 L).…”
Section: Resultssupporting
confidence: 75%
“…PHGDH protein was expressed in resting and stimulated MDDCs. Consistent with the dimerization of PHGDH in the presence of substrate [ 37 ], Western blot carried out in native conditions in a non-denaturing and non-reducing buffer showed the presence of the 55-kD PHGDH band as well as a band compatible with dimerization and constitutive 3-phosphoglycerate flux ( Fig. 6 L).…”
Section: Resultssupporting
confidence: 75%
“…6 in Ref. [40]. Next, experimental traces and simulations of NADH and L-Ser production demonstrated that the former is produced slightly faster at the beginning of the reaction while the concentrations of both products are very close at times ≥ 500 s (Fig.…”
Section: Kinetic Analysis Of the Pp Reactionmentioning
confidence: 74%
“…While the latter change is of small amplitude (2‐fold), the rate of 3PHP production by PHGDH is significantly different between the simulation and the published values. The explanation is provided by recent work [40] demonstrating that the oligomerisation state and the apparent k cat of PHGDH are both altered by the enzyme concentration: The homotetrameric state and the maximal figure of k cat are observed at ≥ 1 μ m enzyme concentration. Actually, the PHGDH kinetic parameters have been previously determined at 0.007 μ m enzyme concentration [31], while present investigations were performed at 0.82 μ m .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, V425M and V490M substitutions are predicted to disrupt core hydrophobic interactions that are important to stabilize the fold of the ASB and ACT domains, respectively. These domains seem essential to regulate the tetrameric assembly of the wild‐type enzyme 36 …”
Section: Resultsmentioning
confidence: 99%